Pengaruh Pemberian Ekstrak Daun Sukun (Artocarpus altilis F.) terhadap Perbaikan Jumlah Sel-Î² Pankreas pada Tikus (Rattus norvegicus) Model Diabetes Melitus - Hidayatulloh, Achmad Syarif; Suyatmi, .; Hikmayani, Nur Hafidha (Nexus Biomedika, 2014)
Background: Diabetes mellitus is a metabolic disorder caused by decrease of insulin production and/or sensitivity. The hyperglycemia state increases free radical production which can damage pancreatic Î² cells through oxidative stress mechanism. Breadfruit leaves contain antioxidants such as flavonoids, phenolics and tannins which can neutralize free radical activity. This study aims to examine the effect of breadfruit leaf extract on pancreatic Î² cells in diabetic rats. Methods: This was an experimental study using posttest only group design. Subjects were 30 male white rats aged 2-3 months and weighed 160-200 g. Subjects were divided into 5 treatment groups. Normal group, treatment group I, II, and III were intraperitoneally induced by 65 mg/kgBW streptozotocine and 230 mg/kgBW nicotinamide. Negative control group and normal group were administered 2 ml/kgBW/day NaCMC, whereas treatment groups I, II, and III were administered breadfruit leaf extract at doses of 200 mg/kgBW/day, 400 mg/kgBW/day, and 800 mg/kgBW/day, respectively. Treatments were conducted for 14 days and rats were terminated at day 15th. The ratsâ pancreases were made into preparations of glass slides with Gomori staining. Data on the numbers of normal pancreatic Î² cells were compared by the Kruskal Wallis test, followed by the Mann-Whitney U tests. Results: There was a significant difference of the numbers of normal pancreatic Î² cells among the groups (p<0.001). Results from Mann-Whitney U tests showed no significant differences, except comparisons between negative control group and treatment group I (p=0.548), and between treatment group III and normal group (p=0.548). Conclusion: Breadfruit leaf extract can improve the numbers of pancreatic Î² cells in diabetic rats with an optimal dose of 800 mg/kgBW/day. Keywords: Breadfruit leaf extract, pancreatic Î² cells, diabetes mellitus, STZ-NA.Â